Nucleolar c‐Myc recruitment by a Vibrio T3SS effector promotes host cell proliferation and bacterial virulence. (21st December 2020) - Hu, Maozhi; Zhang, Yibei; Gu, Dan; Chen, Xiang; Waldor, Matthew K; Zhou, Xiaohui
Abstract: Pathogen type 3 secretion systems (T3SS) manipulate host cell pathways by directly delivering effector proteins into host cells. In Vibrio parahaemolyticus, the leading cause of bacterial seafood‐borne diarrheal disease, we showed that a T3SS effector, VgpA, localizes to the host cell nucleolus where it binds Epstein–Barr virus nuclear antigen 1‐binding protein 2 (EBP2). An amino acid substitution in VgpA (VgpA L10A ) did not alter its translocation to the nucleus but abolished the effector's capacity to interact with EBP2. VgpA‐EBP2 interaction led to the re‐localization of c‐Myc to the nucleolus and increased cellular rRNA expression and proliferation of cultured cells. The VgpA‐EBP2 interaction elevated EBP2's affinity for c‐Myc and prolonged the oncoprotein's half‐life. Studies in infant rabbits demonstrated that VgpA is translocated into intestinal epithelial cells, where it interacts with EBP2 and leads to nucleolar re‐localization of c‐Myc. Moreover, the in vivo VgpA‐EBP2 interaction during infection led to proliferation of intestinal cells and heightened V. parahaemolyticus' colonization and virulence. These observations suggest that direct effector stimulation of a c‐Myc controlled host cell growth program can contribute to pathogenesis. Synopsis: The enteric pathogen V. parahaemolyticus disrupts intestinal barriers and promotes epithelial cell proliferation. This is found here to involve nucleolar recruitment of c‐Myc in host cells via the bacterial type III secretion system (T3SS) effector VgpA. The V. parahaemolyticus T3SS effector VgpA localizes to the nucleolus, where it binds host protein EBP2. VgpA‐EBP2 interaction elevates EBP2's affinity for c‐Myc. VgpA‐EBP2 interaction re‐localizes c‐Myc from the nucleoplasm to nucleolus and increases rRNA expression and cell proliferation. VgpA‐EBP2 interaction during V. parahaemolyticus infection enhances pathogen colonization and virulence in a rabbit infection model. Abstract : The Vibrio parahaemolyticus type III secretion system effector VgpA enhances EBP2/c‐Myc interaction in the host cell nucleolus to promote gut barrier disruption and colonization during infection.